ANALISIS PERAN PELATIH TERHADAP PRESTASI BULUTANGKIS DI KABUPATEN BUNGO - GHAZALI INDRA PUTRA (PRODI PJKR UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2018)
Research began with the decline in the achievements of the badminton sport in Bungo Regency. Achievement is the highest dream of athletes that can be achieved with high motivation. This motivation can come from the athlete's self or external encouragement such as a coach. This research focuses on the role of the trainer on the achievements in badminton. This research is a qualitative research with descriptive method. Data is obtained through observation, interviews and documentation studies. The source of data in this study is the badminton coach at the club under the guidance of PBSI, Bungo Regency. From the results of the data analysis, it can be concluded that the role of the trainer for badminton performance has not run well. In terms of building communication, the trainer has done well. The availability of time for training is still lacking. Short, medium, long-term, age and special single and double training programs are not yet available